ENT 530 Social Media Portfolio: Grafeet Design / Muhammad Fazreen Mohammad Jaafar - Mohammad Jaafar, Muhammad Fazreen (2021)
GRAFEET Design provides graphic design services for their customers. Our business offer affordable services to our beloved customers by giving them a different package with different range of prices. Also, we served our customers with a free of charge consultation for them to meet us before proceeding in designing part. Our target audience is a group of people who are looking design service at low cost and need options with different styles design effect for them to choose in order to meet their preferences. GRAFEET Design also targeting businessman who is about to start new business and in need of ideas for their logos, poster and others. We do not target any specific area because our customers can be from anywhere as long they are seeking for design services. Our services can actually be done and deal online and we do not require to have a face-to-face discussion if it is not convenient for them. The marketing strategy that is used by GRAFEET Design is the lists prices that is provided from the design packages. Whatever guarantee their satisfaction, negotiation on the discount is acceptable. This strategy will attract customer’s attention as we value the customer’s wants and needs. At the moment, GRAFEET Design only owned and work by Muhammad Fazreen Bin Mohammad Jaafar. Our business also use Facebook page and Instagram as a platform for us to attract online customers, gain more awareness and generate more sales at once. We will promote GRAFEET Design by doing teaser post, soft and hard sell as our sale postings on Facebook and Instagram to promote our services.